The Relationship Between Unemployment And Economic Performance Of The Slovak Regions: Does The Disparity Matter? - Ľubomír Darmo (European Scientific Journal, ESJ, 2016)
The Slovak Republic, although it is a relatively young and small state, is a very diverse country. Regional disparities have historical background and persist until nowadays. The most obvious disparities are in the unemployment and the economic performance of regions. On one side, there is more developed west part of the country (the Region of Bratislava is the 6th richest region in the EU) and on the other side, less developed are east (the Region of Prešov) and south regions (the Region of Banská Bystrica). The relationship between unemployment and economic performance, usually measured by the GDP or the GDP growth, is known as Okun´s Law. Thus, the GDP or its growth and unemployment are correlated macroeconomic variables. The aim of the paper is to compare the main macroeconomic variables of the GDP growth and the unemployment rate on the regional basis in the Slovak Republic and to verify the validity of the Okun´s Law in the Slovak Republic on the regional data. Further on, the estimation of Okun coefficients for overall country most developed and less developed regions is made. The result shows that the disparity between regions is evident in the estimated coefficients.